Shallow hydrostratigraphy in an arsenic affected region of Bengal Basin: Implication for targeting safe aquifers for drinking water supply - Biswas, A.; Bhattacharya, P.; Mukherjee, Abhijit; Nath, B.; Alexanderson, H.; Kundu, A.; Chatterjee, D.; Jacks, G. (Elsevier, 2014)
To delineate arsenic (As) safe aquifer(s) within shallow depth, the present study has investigated the shallow hydrostratigraphic framework over an area of 100km 2 at Chakdaha Block of Nadia District, West Bengal. Drilling of 29 boreholes and subsequent hydrostratigraphic modeling has identified three types of aquifer within 50m below ground level (bgl). Aquifer-1 represents a thick paleochannel sequence, deposited parallel to the River Hooghly and Ichamati. Aquifer-2 is formed locally within the overbank deposits in the central floodplain area and its vertical extension is strictly limited to 25m bgl. Aquifer-3 is distributed underneath the overbank deposits and represents an interfluvial aquifer of the area. Aquifer-3 is of Pleistocene age (~70ka), while aquifer-1 and 2 represent the Holocene deposits (age < 9.51ka), indicating that there was a major hiatus in the sediment deposition after depositing the aquifer-3. Over the area, aquifer-3 is markedly separated from the overlying Holocene deposits by successive upward sequences of brown and olive to pale blue impervious clay layers. The groundwater quality is very much similar in aquifer-1 and 2, where the concentration of As and Fe very commonly exceeds 10µg/L and 5mg/L, respectively. Based on similar sediment color, these two aquifers have jointly been designated as the gray sand aquifer (GSA), which constitutes 40% (1.84×10 9 m 3 ) of the total drilled volume (4.65×10 9 m 3 ). In aquifer-3, the concentration of As and Fe is very low, mostly < 2µg/L and 1mg/L, respectively. This aquifer has been designated as the brown sand aquifer (BSA) according to color of the aquifer materials and represents 10% (4.8×10 8 m 3 ) of the total drilled volume. This study further documents that though the concentration of As is very low at BSA, the concentration of Mn often exceeds the drinking water guidelines. © 2014 Elsevier B.V.